(untitled) (Altre Modernità, 2022)
The global pandemic, with its multiple and far-reaching disruptions, has forced us to rethink and rewrite the world we live in. Chris Baker’s novel Kokopu Dreams (2000) sounds somehow prophetic today in the aftermath of the Covid-19 crisis. His work could be labelled as “speculative fiction” and placed among the umbrella categories of magic realism, science fiction and post-apocalyptic fiction. Set in Aotearoa New Zealand, the story focuses on the life of the few human survivors of a rapidly-spreading deadly illness caused by the rabbit calicivirus, illegally introduced into the country. The calicivirus has mutated and killed almost all the human population, who is now living in a land controlled by animals and spirits. The novel is also a template of transcultural writing, mixing Māori creation stories, Christian and Celtic mythologies, scientific issues and aspects of everyday life. Having grown up in a contact zone of different cultures―Baker is of Polynesian (Samoan), Anglo-Saxon and Celtic origin, but regards himself as a “Pacific” person―he shares that multiplicity of belonging which is a typical condition in the Pacific region today. Baker deals with a physical and cultural collective trauma, and the process of re-signification of the ethos in a bi-cultural country made of people of mixed ancestry, European and Māori. The re-elaboration of the epidemic experience is therefore based on both a Western rational representation and an indigenous mythical one.